TECHNOLOGY MANUFACTURING INFLUENCE ON THE TERMOELECTRIC PROPERTIES OF LEAD TELLURIDE AND SOLID SOLUTIONS BASED ON IT - Фреїк, Дмитро Михайлович; Горічок, Ігор Володимирович; Дикун, Наталія Ігорівна; Дзумедзей, Роман Олексійович; Яремій, Іван Петрович; Лисюк, Юрій Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Was research influence of samples preparation method (synthesis mode, size fractions and pressure) on the value of coefficient of thermal e.m.f. for pure of n-and p-PbTe, and doped n-PbTe: Ni (Bi), and solid solutions p-PbSnTe. The correlation between the technological factors, chemical composition, microstructure and thermo-electrical parameters obtained material was receive.